Investment chart patterns when the market needs a rest - Kahn, Michael N. (FTPress delivers elements, 2010)
"This Element is an excerpt from Technical analysis plain and simple: charting the markets in your Language (ISBN: 9780137042012) by Michael N. Kahn. Discover the little-known technical patterns that reveal when the market's headed sideways"--Resource description page.